2019
DOI: 10.1002/cbdv.201900378
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization of Five TunisianEucalyptusEssential Oils Species

Abstract: Hydrodistillation of the dried leaves of five Eucalyptus species, E. alba REINW. ex BLUME, E. citriodora HOOK., E. paniculata SM., harvested from Choucha arboreta (region of Sejnane, northwest of Tunisia), E. pimpiniana MAIDEN from Mjez Elbab arboreta (north east of Tunisia) and E. bicolor A.CUNN ex HOOK from Sidi Smail arboreta (center of Tunisia), in March 2017, afforded essential oils in yields varying from 1.3 � 0.2 to 6.0 � 0.9 % according to the species. E. citriodora provided the highest mean percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…Some studies have reported the composition of the EO of E. alba , even though only one reported that from plants grown in Tunisia. Elaissi and coworkers [ 51 ] reported an EO rich in eucalyptol (44.1%) and appreciable amounts of sesquiterpenes, such as spathulenol (5.8%), globulol (4.9%), and trans -caryophyllene; this composition agrees in part with data recorded in the present study. Our composition generally is consistent with the chemical profiles of the EO of E. alba grown in other countries: Bangladesh [ 52 ], Congo [ 53 ], Senegal [ 54 , 55 ], and Burkina Faso [ 56 ].…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have reported the composition of the EO of E. alba , even though only one reported that from plants grown in Tunisia. Elaissi and coworkers [ 51 ] reported an EO rich in eucalyptol (44.1%) and appreciable amounts of sesquiterpenes, such as spathulenol (5.8%), globulol (4.9%), and trans -caryophyllene; this composition agrees in part with data recorded in the present study. Our composition generally is consistent with the chemical profiles of the EO of E. alba grown in other countries: Bangladesh [ 52 ], Congo [ 53 ], Senegal [ 54 , 55 ], and Burkina Faso [ 56 ].…”
Section: Discussionsupporting
confidence: 92%
“…The examination of E. bicolor EO by Elaissi and coworkers [ 29 ] highlighted similarities in composition with our study, presenting shared compounds such as eucalyptol, aromadendrene, α-pinene, and trans -pinocarveol. While the quantities differed, the commonality in major components highlights consistency in the chemical composition.…”
Section: Discussionsupporting
confidence: 81%
“…For instance, the EO from E. bicolor demonstrated similarity to EO yields from Iraq (1.45 %) as reported by Dehghani et al (2023) [ 28 ]. A separate study conducted in Tunisia indicated 1.50 ± 0.3 % EO yield [ 29 ], while another study from the Province of Isfahan, Iran reported 1.85 % EO yield [ 30 ]. However, for species such as E. amplifolia , E. salubris , and E. campaspe , the yields observed in this study surpass previously documented values.…”
Section: Discussionmentioning
confidence: 99%
“…However, the same authors [ 32 ] reported the composition of an E. paniculata EO with higher amounts (89.8%) of oxygenated components, first of all sesquiterpenes alcohols (τ-cadinol and 7-epi-α-eudesmol), sesquiterpenes oxides (caryophyllene oxide) and monoterpene oxides (eucalyptol). Dorsaf and coworkers [ 3 ] inferred the chemical characterization of a Tunisian EO from E. transcontinentalis ; also in this case, the results displayed eucalyptol as the main component followed by α-pinene.…”
Section: Resultsmentioning
confidence: 99%